Understanding and Managing Conflicts - didi kurniadinata; joni ga selayan; Muhammad Affandi (IULI Publisher, 2023)
Among interpersonal communication skills, managing a conflict is one of the most challenging skillsbecause the conflict often involves emotional elements in the application. Conflicts are everywherethat drain thoughts, emotions and energy. If a conflict is not handled properly, new problems willusually arise and the effects could be worse than expected. If one is a leader, the ability to manageconflict is very important. According to a research conducted by The American ManagementAssociation, 20 percent of a leader's time is used to manage conflict. Meanwhile, research resultsfrom the Queensland Government show that more time, namely 30% of manager's time, is used toresolve conflicts in the office. A conflict is due to the differences that arise both in the views andinterests of people in formal or social interactions. The differences which have become conflicts resultin incompatibility and disagreement. Since the incompatibility and disagreement use up abundantenergy, traditional views mention that (1) conflict should be avoided because it will use not onlyenergy but create cost as well. However, the people with the human relations view consider that (2)conflict is something natural and it normally occurs in any organisation. Moreover, the interactionistgroup views that (3) conflict is a necessary and positive force that is imminent for an organisation toperform more effectively. Keywords: Conflict; Interpersonal Communication; Human Relations; Values; Leadership